Use of Information and Communication Technology (ICT) across the Vegetable Value Chain in Chitwan, Nepal - Neupane, Suman; Bhatta, Sushmita; Mishra, Binayak Prakash (Journal of Agriculture and Forestry University, 2025)
Integration of Information and Communication Technology (ICT) is essential for enhancing agricultural value chains, with improved efficiency, stronger coordination, and timely access to reliable information. This study examined ICT use across the vegetable value chain in Chitwan, Nepal, focusing on device ownership, platform utilization, perceived benefits, challenges, and digital literacy among input suppliers, farmers, collectors, wholesalers, retailers, and consumers. Data were collected from 134 farmers and 58 other value chain actors using a semi-structured interview schedule and analyzed through frequency calculation. Results revealed universal ownership of mobile phones, radios, and televisions, but farmers’ access to smartphones and the internet was lower than that of other actors. Farmers mainly used ICT for crop calendars and real time market prices, while other actors extensively employed ICT for market communication, logistics, and price negotiation. Although 73.13% of farmers reported improved decision making, only 37.31% observed higher income. Key challenges among farmers included lack of training, language barriers, and irrelevant content. No actors had received formal ICT training, and farmers’ digital literacy was lower than that of input suppliers and wholesalers. The study highlights a critical need for targeted ICT training, localized content, and improved extension services to enhance digital literacy and facilitate effective ICT adoption, thereby increasing the associated benefits within the vegetable value chain.